Role of Nampt and Visceral Adiposity in Esophagogastric Junction Adenocarcinoma. (11th January 2017) - Li, Haijun; Bai, E.; Zhang, Yong; Jia, Zhuoqi; He, Shicai; Fu, Junke
Abstract : Nampt including eNampt and iNampt may contribute to mediating obesity-associated cancers. This study investigated the role of Nampt in esophagogastric junction adenocarcinoma (EGA), a cancer strongly correlated with obesity. Visceral adiposity was defined by waist circumference or VFA. eNampt in sera were measured by enzyme-linked immunosorbent assay. iNampt expression in EGA was determined by PCR, western blot, and immunohistochemistry. Sera eNampt were significantly elevated in these overweight and obese patients, especially for viscerally obese patients, and positively correlated with BMI, waist circumference, VFA, and also primary tumor, regional lymph nodes, and TNM stage (P < 0.05 ). iNampt expression in both the mRNA and protein levels was upregulated in EGAs (P < 0.05 ). iNampt staining was found primarily in the cytoplasm and nuclei and significantly associated with tumor, lymph nodes, and TNM stage and also correlated positively with serum eNampt, BMI, total fat area, VFA, superficial fat area, and waist circumference (P < 0.05 ). iNampt, eNampt, tumor, lymph nodes, and TNM stage correlated to the survival of EGAs, and iNampt expression and TNM stage affected the prognosis independently (P < 0.05 ). This study highlighted the association of eNampt/iNampt with visceral obesity and a potential impact on the biology of EGA.